THE INFLUENCE OF ADAPTABILITY AND MISSION ON ACADEMIC STAFF PERFORMANCE IN UNIVERSITAS WIDYATAMA - Suharno Pawirosumarto; Muhammad Geraldo Marsatiorozen; M Mutmainnah (Erudio Journal of Educational Innovation, 2022)
This research aimed to determine the influence of organizational culture (adaptability and mission) on the academic staff performance in Universitas Widyatama (UTama). The research population was 188 employees. We determined respondents using the Slovin formula. We obtained 66 respondents. The research was quantitative, employing multiple linear regression analysis and the SPSS program to analyze the data. The research result showed that adaptability and mission simultaneously have a positive and significant influence on UTama education staff performance. Future research needs to study other aspects of organizational cultures, such as engagement and consistency and may use engagement and consistency in correlation to performance variables. Future research may also use all aspects of organizational culture (engagement, consistency, adaptability, and mission) to study employee performance.